Validação do “Sarcopenia and Quality of Life” (SarQoL ® ) para o contexto brasileiro - Nunes, Juliana Duarte (2020)
Introduction: Sarcopenia is a chronic condition associated with the physiological aging process and is defined by the reduction of muscle mass, strength and function. Recently, a specific quality of life assessment instrument for people with sarcopenia called Sarcopenia and Quality of Life (SarQoL® ) was created and its Brazilian version has already been translated and adapted, with the validation stage missing for the availability of the instrument in Brazil. Objective: to validate the instrument “Sarcopenia and Quality of Life” (SarQoL® ) in Brazil with elderly people in the community. Methodology: this was a methodological study to validate SarQoL® in Brazil and for this process, the steps recommended by the authors of the SarQoL® instrument were followed. Respecting the inclusion and exclusion criteria previously established, the elderly were invited to participate in the study by telephone and once accepted, an individual interview was conducted, with the application of SarQoL® , from the Medical Outcomes Study 36 - Item Short Form Health Survey (SF-36), EuroQol-5D (EQ-5D), Mini Nutritional Assessment (MAN), Mini Mental State Examination (MMSE) and Geriatric Depression Scale (GDS). For the diagnosis of sarcopenia, the procedure recommended by the Second European Sarcopenia Consensus (EWGSOP2) published in 2019 was followed, in which initially muscle strength is checked (in this study, hand grip strength was used), and to confirm sarcopenia, muscle mass (verified in this study by DXA). The study was formally authorized and approved by the Research Ethics Committee of the Federal University of São Carlos - UFSCar under opinion n.637.779 / 2016. Results: of the 221 elderly participants in the survey, 68.3% were women (n = 151), with an average schooling of 5.4 years, 163 participants were white (73.8%) and 61.1% were married (n = 135). Regarding sarcopenia, 55 elderly people presented sarcopenia according to the criteria of the EWGSOP2. Among the psychometric properties that were verified for the validation of the Brazilian version of SarQoL® , there is reliability, through the internal consistency verified by Cronbach's alpha coefficient, in which the total of SarQoL® was 0.976, indicating excellent internal consistency, and also by the test-retest, verified by means of the intraclass correlation coefficient (ICC), in which the ICC of 0.983 (95% CI 0.901-0.996) was observed in the total SarQoL® , also demonstrating good reliability. In construct validity, SarQoL® was correlated with SF-36 and EQ-5D, generally identifying a positive correlation of moderate to strong magnitude and all correlations were statistically significant. In the discriminant validity, the quality of life of patients with and without sarcopenia was compared, with the elderly with sarcopenia having an average total score of 55.57, compared to a score of 73.94 in the elderly without sarcopenia. All elderly people with sarcopenia had lower scores in all domains of SarQoL® , as well as in total, and all values had a significant p-value, showing good discriminant validity. Conclusion: Based on the proposed objective and the results obtained, it can be concluded that SarQoL® has evidence of reliability and validity. SarQoL® translated, adapted and validated in the Brazilian context is available for use in Brazil.